Character Education in Islamic Sufism Perspective - Sarim Karimullah, Suud (Prodi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah IAI Hamzanwadi NW Pancor, 2023)
Abstract This study comprehensively explores the role and relevance of Sufism-based approaches to character education as a valuable framework for shaping individual and community character from an Islamic perspective. This study uses the literature study method with an integrative literature analysis approach to obtain comprehensive results in identifying and evaluating critical concepts related to character education from the perspective of Islamic Sufism. The results of this study stated that character education based on Islamic Sufism has excellent potential to form individuals who are responsible, moral, and ethical. Through a basic understanding of Sufism in character education, individuals are taught to have a profound moral awareness and strong ethical values as the foundation of their actions. The practice of Sufism in character education creates individuals who are more humble, thoughtful, and able to reflect on their activities honestly and focus on continued personal growth. Applying Sufism-based character education in everyday life connects moral and ethical principles with concrete steps in society, creating better relationships with fellow human beings, nature, and the spiritual world. Thus, character education based on Islamic Sufism can positively contribute to creating a more inclusive, fair, peaceful, and harmonious society in an increasingly complex world. Abstrak Kajian ini secara komprehensif mengeksplorasi peran dan relevansi pendekatan pendidikan karakter berbasis tasawuf sebagai kerangka kerja yang berharga untuk membentuk karakter individu dan masyarakat dalam perspektif Islam. Kajian ini menggunakan metode studi pustaka dengan pendekatan analisis literatur secara integratif untuk mendapatkan hasil yang komprehensif dalam mengidentifikasi dan mengevaluasi konsep-konsep kunci yang terkait dengan pendidikan karakter dalam perspektif tasawuf Islam. Hasil kajian ini menyatakan bahwa pendidikan karakter berbasis tasawuf Islam memiliki potensi besar untuk membentuk individu yang bertanggung jawab, bermoral, dan beretika. Melalui pemahaman dasar tasawuf dalam pendidikan karakter, individu diajarkan untuk memiliki kesadaran moral yang mendalam dan nilai-nilai etika yang kuat sebagai landasan tindakan mereka. Praktik tasawuf dalam pendidikan karakter menciptakan individu yang lebih rendah hati, bijaksana, dan mampu merenungkan tindakan mereka dengan kejujuran serta berfokus pada pertumbuhan pribadi yang berkelanjutan. Penerapan pendidikan karakter berbasis tasawuf dalam kehidupan sehari-hari menghubungkan prinsip-prinsip moral dan etika dengan tindakan konkret dalam masyarakat, menciptakan hubungan yang lebih baik dengan sesama manusia, alam, serta dunia spiritual. Dengan demikian, pendidikan karakter berbasis tasawuf Islam dapat memberikan kontribusi positif dalam menciptakan masyarakat yang lebih inklusif, adil, damai, dan harmonis di tengah dunia yang semakin kompleks.